Triage of human papillomavirus infected women by methylation analysis in first-void urine - Van Keer, Severien (Sci Rep, 2021)
Host cell DNA methylation analysis in urine provides promising triage markers for women diagnosed with a high-risk (HR) human papillomavirus (HPV) infection. In this study, we have investigated a panel of six host cell methylation markers (GHSR, SST, ZIC1, ASCL1, LHX8, ST6GALNAC5) in cervicovaginal secretions collected within the first part of the urine void (FVU) from a referral population. Cytology, histology, and HPV DNA genotyping results on paired FVU and cervical samples were available. Urinary median methylation levels from HR-HPV (n = 93) positive women were found to increase for all markers with severity of underlying disease. Significantly elevated levels were observed for GHSR and LHX8 in relation to high-grade cervical intraepithelial neoplasia (CIN2 +; n = 33), with area under de curve values of 0.80 (95% Confidence Interval (CI) 0.59–0.92) and 0.76 (95% CI 0.58–0.89), respectively. These findings are the first to support the assertion that methylation analysis of host cell genes is feasible in FVU and holds promise as molecular, triage strategy to discern low- from high-grade cervical disease in HR-HPV positive women. Molecular testing on FVU may serve to increase cervical cancer screening attendance in hard-to-reach populations whilst reducing loss to follow-up and await further optimization and validation studies.